Did Prince Cetshwayo read the Old Testament in 1859? The role of the Bible and the art of reading in the interaction between Norwegian missionaries and the Zulu elite in the mid-19th century - Holter, Knut (Old Testament essays, 2009)
The context of this essay is the celebration of 150 years of theological - including Old Testament - studies in South Africa, commemorating the establishing of a theological seminary in Stellenbosch in 1859. The essay discusses another but simultaneous incident reflecting the early interface between South Africa and the Bible. In late 1859, the Zulu Prince (later King) Cetshwayo approached Norwegian missionaries operating at the border between Natal and Zululand, expressing his wish to learn to read. The missionaries saw this as a God-given opportunity to expose the prince to the Word of God, and Moses, a Christian Zulu, was put in charge of the instruction. Based on Norwegian (and to some extent British: Colenso) missionary sources, the essay discusses this incident in 1859 from the perspective that the Bible is perceived by both missionaries and Zulus as a particular object of power, within the more general exchange of goods and services between the missionaries and the Zulu elite.